2020
DOI: 10.1017/s135732172000015x
|View full text |Cite
|
Sign up to set email alerts
|

Managing uncertainty: Principles for improved decision making

Abstract: Effective management of uncertainty can lead to better, more informed decisions. However, many decision makers and their advisers do not always face up to uncertainty, in part because there is little constructive guidance or tools available to help. This paper outlines six Uncertainty Principles to manage uncertainty. Face up to uncertainty Deconstruct the problem Don’t be fooled (un/intentional biases) Models can be helpful, but also dangerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Uncertainty refers to the state of mind to be unsure or doubtful about someone or something. It can be either about an outcome, any questions asked, the context of the issue or the dynamics of a problem and generally, its effect is considered as a negative phenomenon Kaye et al (2020). The results confirmed that uncertainty does not moderate any of the relationships hypothesized between four predictors of behavioral intention.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Uncertainty refers to the state of mind to be unsure or doubtful about someone or something. It can be either about an outcome, any questions asked, the context of the issue or the dynamics of a problem and generally, its effect is considered as a negative phenomenon Kaye et al (2020). The results confirmed that uncertainty does not moderate any of the relationships hypothesized between four predictors of behavioral intention.…”
Section: Discussionmentioning
confidence: 55%
“…This scale was developed in accordance with the definition of uncertainty given in the literature review. It was difficult to adopt any previously studied scale as the dimensions of the variable change with the change in context and situation (Kaye et al , 2020). All of the constructs are measured on a five-point Likert scale from 1 (strongly disagree) to 5 (strongly agree) ranges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ill-structured problems arise in all facets of life, this has led to many studies in different domains, for example in psychology (e.g. Frensch and Funke 1995;Stadler et al 2019), design thinking (Goel and Pirolli 1992;Buchanan 1992;Conklin 2006;Brown 2008;Kolko 2015;Micheli et al 2019), instructional design (Jonassen 1997(Jonassen , 2000 McDonald and Yanchar 2020), project management (Ahern et al 2014; Mikkelsen 2020), business decision-making (Snowden 2002;Kaye et al 2020) and engineering education (Dringenberg and Purzer 2018;Wolff 2020).…”
Section: Dealing With Problem Situationsmentioning
confidence: 99%